2022
DOI: 10.33308/26674874.2022363453
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrencilerinde Oyun Bağımlılığı ile Sorumluluk Duygusu-Davranışı ve Sosyal Beceriler

Abstract: Bu araştırmanın amacı ortaokul öğrencilerinde oyun bağımlılığı ile sorumluluk duygusu-davranışı ve sosyal beceri arasındaki ilişkiyi incelemektir. Çalışma 341 (%68.2) kız, 159 (%31.8) erkek olmak üzere toplam 500 öğrenci üzerinde yapılmıştır. Araştırmada veri toplama aracı olarak, Sorumluluk Duygusu ve Davranışı Değerlendirme Ölçeği (SSDÖ),  Ergenler İçin Oyun Bağımlılığı Ölçeği, Sosyal Beceriler Ölçeği ve araştırmacının oluşturduğu kişisel bilgi formu kullanılmıştır. Elde edilen veriler İlişkisiz Grup t Testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Research conducted by Arslan ( 2021 ) found that secondary school students’ sense of responsibility and behavior had a crucial predictive role in online gaming addiction. Another study reported a significant negative relationship between the students’ videogame addiction and their personal and social responsibility behavior (Dinçer & Kolan, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research conducted by Arslan ( 2021 ) found that secondary school students’ sense of responsibility and behavior had a crucial predictive role in online gaming addiction. Another study reported a significant negative relationship between the students’ videogame addiction and their personal and social responsibility behavior (Dinçer & Kolan, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…When basic psychological needs are not met, it pushes individuals to exhibit maladaptive behavioral reactions (i.e., online gaming addiction) (Bekir & Çelik, 2019 ). In addition, few studies have addressed the relationship between responsibility and meaning in life and online game addiction (Arslan, 2021 ; Kaya, 2021 ). Moreover, no study has ever examined the mediating role of responsibility and meaning in life in the relationship between basic psychological needs and online game addiction.…”
Section: Introductionmentioning
confidence: 99%